Focus on the success of others leads to selfish behavior - van den Berg, Pieter; Molleman, Lucas; Weissing, Franz J. (National Academy of Sciences, 2015)
It has often been argued that the spectacular cognitive capacities of humans are the result of selection for the ability to gather, process, and use information about other people. Recent studies show that humans strongly and consistently differ in what type of social information they are interested in. Although some individuals mainly attend to what the majority is doing (frequency-based learning), others focus on the success that their peers achieve with their behavior (success-based learning). Here, we show that such differences in social learning have important consequences for the outcome of social interactions. We report on a decision-making experiment in which individuals were first classified as frequency and success-based learners and subsequently grouped according to their learning strategy. When confronted with a social dilemma situation, groups of frequency-based learners cooperated considerably more than groups of success-based learners. A detailed analysis of the decision-making process reveals that these differences in cooperation are a direct result of the differences in information use. Our results show that individual differences in social learning strategies are crucial for understanding social behavior.